HUBUNGAN ANTARA PEMBELAJARAN AKIDAH AKHLAK DENGAN PERILAKU SOPAN SANTUN PESERTA DIDIK DI MADRASAH TSANAWIYAH AL-MURAHAMAHTUL ISLAMIYAH BANYORANG KECAMATAN TOMPOBULU KABUPATEN BANTAENG - Nurhidayah; Muhammad Amri; Salahuddin; Nuryamin; Besse Ruhaya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The indication of the low level of students’ polite behavior can still be seen from several students who display impolite attitudes, such as using inappropriate words, being unserious and tending to joke around during Aqidah Akhlak learning activities, and showing indifferent attitudes when meeting or passing by teachers. This thesis aims to: 1) describe the Aqidah Akhlak learning activities at Madrasah Al-Murahamahtul Islamiyah, Bantaeng Regency; 2) describe the polite behavior of students at Madrasah Al-Murahamahtul Islamiyah, Bantaeng Regency; and 3) analyze whether there is a relationship between Aqidah Akhlak learning and students’ polite behavior at Madrasah Al-Murahamahtul Islamiyah, Bantaeng Regency.This study employed a quantitative ex post facto method with a simple linear regression research design. The research was conducted at Madrasah Tsanawiyah Al-Murahamahtul Islamiyah Banyorang, Tompobulu District, Bantaeng Regency. The population of this study consisted of 73 students at Madrasah Tsanawiyah Al-Murahamahtul Islamiyah Banyorang, Tompobulu District, Bantaeng Regency. Based on the calculation results, the value of tcount = 2.276, while ttable = 1.666 at a significance level of 0.05. Since tcount was greater than ttable, it can be concluded that H0 was rejected and H1 was accepted. This means that there is a relationship between Aqidah Akhlak learning and the polite behavior of students at Madrasah Tsanawiyah Al-Murahamahtul Islamiyah Banyorang, Bantaeng Regency.